The Church as an agent of secularization. Municipalities and concordat in El Salvador, 1842-1862 - González Torres, Julián (Realidad: Revista de Ciencias Sociales y Humanidades, 2020)
This paper analyzes the role of the Salvadoran Catholic Church as an agent of secularization. From the analysis of the relations of collaboration, tension and conflict between the Diocese of San Salvador and the municipalities of the state, and from the analysis of the concordat signed between the Salvadoran State and the Holy See (1862). This research reveals that in the process of secularization the Catholic Church served as an agent and as a product of that process. Realidad: Revista de Ciencias Sociales y Humanidades No. 156, 2020: 83-111